2012
DOI: 10.1128/jcm.05588-11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Microbiological Characterization of Clostridium difficile Isolates from Single, Relapse, and Reinfection Cases

Abstract: In this study, we investigated the correlation between the microbiological characteristics of Clostridium difficile clinical isolates and the recurrence of C. difficile-associated disease (CDAD). Twenty C. difficile isolates recovered from 20 single infection cases and 53 isolates from 20 recurrent cases were analyzed by pulsed-field gel electrophoresis (PFGE) and PCR ribotyping, and the cytotoxicity, antimicrobial susceptibility, and sporulation/germination rates of the isolates were examined. Recurrent cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 49 publications
3
48
0
4
Order By: Relevance
“…22) Another previous study also showed that all 73 isolates were susceptible to both metronidazole and vancomycin. 23) Thus, C. difficile isolates in Japan appear to be susceptible to both agents. In the present study, no significant difference was observed in the cure rate between vancomycin and metronidazole (Tables 2, 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22) Another previous study also showed that all 73 isolates were susceptible to both metronidazole and vancomycin. 23) Thus, C. difficile isolates in Japan appear to be susceptible to both agents. In the present study, no significant difference was observed in the cure rate between vancomycin and metronidazole (Tables 2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…26) Among the 20 recurrent cases examined, 16 cases (80%) were identified as cases of recurrence caused by the initial strain while the remaining 4 cases (20%) were identified as reinfection cases by different strains; therefore, Oka et al suggested that the germination ability of C. difficile may be a potential risk factor for the recurrence of CDI. 23) Cancer chemotherapy is a risk factor for CDI that is mediated by the antimicrobial activity of several chemotherapeutic agents 10,27) and could also be related to the immunosuppressive effects of neutropenia. 28,29) The risk of recurrent disease has been shown to be related to the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly pre-scribed antimicrobial therapy for C. difficile infection is metronidazole or oral vancomycin. As the concentrations of these drugs in the feces are typically high, treatment failures are rarely thought to be due to resistance of the organisms to the antimicrobial therapy (34,170). However, metronidazole concentrations in the stool can be variable depending on the consistency of the stool and the amount of inflammation in the gut.…”
Section: Evolution Of Testing Methodsmentioning
confidence: 99%
“…Las esporas de C. difficile que no fueron eliminadas en las deposiciones pueden persistir en el tracto colónico del paciente, lo que pudiese favorecer los episodios de recurrencia de IACD. Los eventos de recurrencia de IACD se pueden clasificar como: recaída, si es causada por la misma cepa responsable del primer episodio, lo que representan ~75% de las recurrencias; re-infección, si es causada por una cepa diferente a la del episodio inicial, con una frecuencia de ~25% de todos las recurrencias 3 . En ambos casos, la recurrencia de IACD se vería favorecida por una modificación extrema de la microbiota colónica y la consecuente alteración de los mecanismos de defensa intrínsecos de esta microbiota contra de las infecciones por bacterias patógenas 29,30 .…”
Section: Departamento De Laboratoriounclassified
“…El cuadro clínico de las IACD puede ir desde una diarrea leve y auto limitada hasta una colitis fulminante con pseudomembranas y megacolon tóxico 2 . La tasa de mortalidad de las IACD es aproximadamente de 5%; sin embargo, uno de los mayores problemas de las IACD es su elevada tasa de recurrencia, la que puede alcanzar tasas de 20% después de un primer episodio 3 . Clostridium difficile secreta dos principales factores de virulencia, la enterotoxina TcdA y la citotoxina TcdB 4 .…”
Section: Introductionunclassified